Fatality due to unusual femoral vein rupture in an injectable drug user - Yadav, Abhishek; Aravindan , V; Abilash, S; Gupta , Sudhir K (Journal of Indian Academy of Forensic Medicine, 2021)
Drug addiction is an ever-increasing evil in society. Injectable drug users have a high risk of complications. There is a wide variety of  presentations and complications of such addiction cases. Deaths are reported in drug users most frequently due to acute  intoxication/overdose and related complications. Intravenous drug intake leading to rupture of a vein is seldom reported in the  literature. We report a rare case in which a drug addict collapsed after a burst of drug kit following injection into his right thigh and  died. The authors aim to highlight and spread awareness in society about such unknown uncommon accidental dangers associated  with injectable drug abuse which could be fatal. The authors also aim to aid to Medical Literature such rare episodic occurrences  which could cause fatality in drug users.
Keywords: Femoral vein rupture; Hemorrhagic shock; Drug abuse; Injectable Drugs user; Substance abuse; Drug Kit